2019
DOI: 10.1002/aic.16574
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic and molecular insights into the absorption of H2S, CO2, and CH4 in choline chloride plus urea mixtures

Abstract: Deep eutectic solvents (DESs) are a class of promising media for gas separation. In order to examine the potential application of DESs for natural gas upgrading, the solubilities of H2S, CO2, and CH4 in choline chloride (ChCl) plus urea mixtures were measured in this work. The solubility data were correlated with Henry's law equation to calculate the thermodynamic properties of gas absorption processes, such as Henry's constants and enthalpy changes. Grand‐canonical Monte Carlo simulations and quantum chemistr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(49 citation statements)
references
References 63 publications
1
44
0
4
Order By: Relevance
“…Thus, DESs are widely regarded as a new class of IL analogues. Many previous studies have demonstrated the applications of DESs in the absorption of CO 2 , 14 NH 3 , 15,16 and H 2 S 17 . Up to now, there has been less mention of using DESs for efficient absorption of CO.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, DESs are widely regarded as a new class of IL analogues. Many previous studies have demonstrated the applications of DESs in the absorption of CO 2 , 14 NH 3 , 15,16 and H 2 S 17 . Up to now, there has been less mention of using DESs for efficient absorption of CO.…”
Section: Introductionmentioning
confidence: 99%
“…Since the research to date on the application of DESs for CO 2 capture has been restricted to the gas adsorption, solubility, and other physicochemical properties of DESs, further more systematic explorations into the mechanism of CO 2 ‐DES system and attempts at the DESs‐based CO 2 separation membrane fabrication have remained to be made . To the best of our knowledge, the rollout and the only report of DES‐based membrane so far for the purpose of CO 2 separation was polyvinylidene fluoride‐ co ‐polytetrafluoroethylene/DES supported membrane prepared by incorporation of choline chloride/ethylene glycol (ChCl/EG) DES into polymeric membrane pores and achieved a CO 2 permeance of 25.5 × 10 3 GPU (gas permeation unit, 1 GPU = 1 × 10 −6 cm 3 (STP) cm −2 s −1 cmHg −1 ) but with separation factor of only 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al [ 124 ] found that H 2 S absorption capacity increased with increasing molar ratio of ChCl/urea DES from 1:1.5 to 1:2.5 at a fixed temperature and pressure. Furthermore, the absorption capacity of H 2 S in ChCl/urea DESs was decreased linearly by increasing the temperature.…”
Section: Capture Of Acidic Gasesmentioning
confidence: 99%